2002
DOI: 10.1177/002580240204200209
|View full text |Cite
|
Sign up to set email alerts
|

Did He Drown or was He Murdered?

Abstract: An unemployed, 60-year-old Singaporean gentleman died during a brief overseas trip to another South-East Asian country. He had, presumably, drowned in the bathtub of his hotel room, which he shared with his then 44-year-old companion, who was supposedly his nephew. The relevant public health and medico-legal authorities of the host country conducted an external examination of the body at the scene, whereupon they agreed with the police that his death was probably due to accidental drowning following an episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It was reported that an unemployed, 60 years old Singaporean man had drowned in the bathtub of his hotel room during a brief overseas trip with his nephew (extracted from Lau, 2002). It was concluded that the deceased death was probably due to accidental drowning and that this was arrived heavily based on circumstantial and hearsay evidence.…”
Section: Fraud In Travel Insurancementioning
confidence: 99%
“…It was reported that an unemployed, 60 years old Singaporean man had drowned in the bathtub of his hotel room during a brief overseas trip with his nephew (extracted from Lau, 2002). It was concluded that the deceased death was probably due to accidental drowning and that this was arrived heavily based on circumstantial and hearsay evidence.…”
Section: Fraud In Travel Insurancementioning
confidence: 99%
“…Considering these significant numbers, deaths in these establishments due to incidents, accidents, and natural causes are seen from time to time. From alcohol, drug, or carbon monoxide intoxications, to drownings, falls, or cardiovascular diseases, different manners and causes of death have been reported in the literature from all over the globe [3][4][5][6][7][8]. It has been suggested, similar to private properties, that deaths can make hotel rooms lose value and stigmatize them in guests' eyes [9], which may cause serious problems for the hotel and tourism industry.…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned reports and articles on this topic consist mainly of a limited number of cases [3,6,8,10]. Only a few studies included various causes of death, and unfortunately, these studies did not have large populations.…”
Section: Introductionmentioning
confidence: 99%